Parenting Education Of Perspective T.M Hasbi Ash-Shiddieqy (Analytical Study In Tafsir Al-Qur'ān Al-Majīd An-Nūr Qs. Al-Isrā '[17]: 22-39) - Rohmah, Miftahur; Innayati, Nafisah (WISDOM: Jurnal Pendidikan Anak Usia Dini, 2023)
This paper discusses parenting education from the perspective of the Indonesian interpreters, Hasbi Ash-Ashiddieqy. The purpose of this study is to map the application of parenting education contained in QS.Al-Isrā' [17]: 22-39. This study uses a qualitative descriptive analysis method with munasabah verses. The result of this study found five implementations of parenting education from the perspective of Hasbi Ash-Shiddieqy. The first is always remembering Allah, the second is devoted to parents, the third is doing well to others, the fourth is spending wealth properly, and the last is not violating the Shari'a. The essence of implementing parenting education is the importance of hablumminallah wa hablumminannas. Five parenting education points that parents can apply are instilling monotheism and faith from an early age, teaching manners, , providing knowledge in managing finances from an early age, and providing guidance to children about the differences between commendable behavior and despicable.